How gamification in virtual reality affects brand coolness and marketing outcomes - Stein, F. (2023)
Description: The current study shows that hedonic and social values enhance perception of brand coolness and that utilitarian value was found not to affect brand coolness in a VR environment with a gamification experience, however, brand coolness affects brand preference and customer loyalty in such environment.